The inhibition of human farnesyl pyrophosphate synthase by nitrogen-containing bisphosphonates. Elucidating the role of active site threonine 201 and tyrosine 204 residues using enzyme mutants - Tsoumpra, MK; Muniz, JR; Barnett, BL; Kwaasi, AA; Pilka, ES; Kavanagh, KL; Evdokimov, A; Walter, RL; Von Delft, F; Ebetino, FH; Oppermann, U; Russell, RGG; et al. (Elsevier, 2015)
Farnesyl pyrophosphate synthase (FPPS) is the major molecular target of nitrogen-containing bisphosphonates (N-BPs), used clinically as bone resorption inhibitors. We investigated the role of threonine 201 (Thr201) and tyrosine 204 (Tyr204) residues in substrate binding, catalysis and inhibition by N-BPs, employing kinetic and crystallographic studies of mutated FPPS proteins.